2019
DOI: 10.1007/s00468-019-01898-3
|View full text |Cite
|
Sign up to set email alerts
|

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density

Abstract: We examined crown architecture and within crown leaf area distribution effects on Pinus taeda L. growth in North Carolina (NC), Virginia (VA), and Brazil (BR) to better understand why P. taeda can grow much better in Brazil than in the southeastern United States. The NC, VA, and BR sites were planted in 2009, 2009, and 2011, respectively. At all sites, we planted the same two genetic entries at 618, 1236, and 1854 trees ha −1 . In 2013, when trees were still open grown, the VA and NC sites had greater branch d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Finally, the maximum number of leaves per plant (116) was recorded from treatment (T1). These results are in agreement with findings by Albaugh et al [15] reporting in higher plant densities can be observed a lower number of leaves, branches [16] reported the minimum number of leaves per plant of green pepper was recorded from the closest spacing which was however statistically similar to the widest spacing. The measurements made on plant components show that more leaves were observed as plant population reduced probably in relation to lower competition for physical production resources (soil moisture and nutrients) which would enhance nutrient availability and efficient utilization of assimilates.…”
Section: Plant Height Stem Girth and Number Of Leavessupporting
confidence: 93%
“…Finally, the maximum number of leaves per plant (116) was recorded from treatment (T1). These results are in agreement with findings by Albaugh et al [15] reporting in higher plant densities can be observed a lower number of leaves, branches [16] reported the minimum number of leaves per plant of green pepper was recorded from the closest spacing which was however statistically similar to the widest spacing. The measurements made on plant components show that more leaves were observed as plant population reduced probably in relation to lower competition for physical production resources (soil moisture and nutrients) which would enhance nutrient availability and efficient utilization of assimilates.…”
Section: Plant Height Stem Girth and Number Of Leavessupporting
confidence: 93%
“…Growth efficiency (the efficiency with which an individual tree makes use of site resources to produce stem biomass) as well as LAI have been considered across sites with variability such as these before, with responses to silviculture being most apparent on nutrient-deficient, poorly drained sites like RW20-NC [40]. Albaugh et al (2019) specifically explored the growth efficiency and crown dynamics of RW20 sites, concluding that unexplored site variables are causing the large degree of variance in crown architecture, crown leaf area distribution, and individual tree growth efficiency between individual sites [41]. The ideal training dataset would cover as broad of a geographic range as possible to account for variety in loblolly pine's native range.…”
Section: Model Performance and Interpretationsmentioning
confidence: 99%
“…The spatial distribution of foliage biomass is also a crucial characteristic of canopy architecture because the amount and distribution of intercepted radiation intrinsically depend on the crown structure of the individual trees [43,44]. The importance of the vertical distribution of foliage biomass has already been emphasized for Douglas fir [45,46], jack pine [34], and loblolly pine [18].…”
Section: Discussionmentioning
confidence: 99%
“…Light interception drives tree growth and so growth is generally related to leaf area [17]. Specific tree species with a high number of branches and high branch biomass exhibit greater productivity because they are able to develop a crown with a higher leaf area [18]. The leaf area of an individual tree is therefore closely related to photosynthesis and productivity [19].…”
Section: Introductionmentioning
confidence: 99%